The effect of building height on thermal properties and comfort of a housing project in the hot arid climate of the UAE - Salameh, Muna; Elkhazindar, Ayat; Touqan, Basim (Frontiers in Built Environment, 2023)
A city’s microclimate is greatly impacted by urbanization. The ratio of building height to street width affects the thermal properties of urban canyons. This characteristic is one of the main elements that control the thermal radiation emitted and how much solar radiation is absorbed, causing the urban air temperature to be much greater than in rural areas (urban heat island effect). The main aim of this study is to examine the thermal effect of the variations in the height of housing buildings on the urban layout and canyons in the hot arid climate of the UAE. The study used a qualitative method based on ENVI-met software and a case study of an existing housing project to investigate the current situation and the future thermal conditions of proposed configurations. The study investigated two groups of configurations with unified and diverse heights. The results of the study found that the best case among the first group of configurations with unified heights was U3, which had unified mass heights reaching 20 m height, the highest H/W ratio, and the lowest sky view factor; it recorded 0.5°C reduction in the 2:00 p.m. air temperature compared to the base case. The results also revealed that in the case of diverse heights, it is better to locate the highest masses in the hot wind direction. The D2, with highest masses of 20 m height that were located only on the north and west sides of the area blocking the hot north-west prevailing wind, recorded a reduction about 0.9°C compared to the base case. Moreover, in the cases with lower air temperature, U3 and D2 recorded the best predicted mean vote readings, especially in the daytime, when the air temperature is highest.